Acceptance of low-sodium diet and nutritional status by hospitalized patients in the Public Hospital of Goiania - Dacal Mattos Casado, Andréa Valéria; Silva Barbosa, Larissa (O Mundo da Saúde, 2015)
Hospital malnutrition is a global public health problem and it can reach up to 50% of the hospitalized individuals. The inadequate intake of nutrients compromises the nutritional status of the patient and increases the prevalence of malnutri- tion. The low-sodium diets are not well accepted by the hospitalized individuals, and the elimination or reduction of salt determines its low acceptance. The present study aimed to verify the acceptance of the low-sodium diet by hospitalized patients in the Public Hospital of Goiania, Goiás. This was a cross-sectional study with 33 adults and elderly patients of both genders that on the day of evaluation received low-sodium diet. The study was approved by the Research Ethics Com- mittee of the Emergency Hospital of Goiania (Protocol n° 049/09). The greatest number of patients were female (57.6%), 50% of the elderly were low weight. The meals served were considered as “good” by 69.7% of the population studied and had a pleasant flavor for the 81.8% of the hospitalized. Through the technique of direct observation was evaluated the acceptance of meals offered at lunch and dinner. The results revealed that in the two meals, most patients ingested less than half (<1/2) of the offered portion. We concluded that despite that low ingestion, most individuals revealed that the diet offered had taste and correct temperature and, therefore, had good acceptance. However, it has been suggested that new techniques be tested and adapted to hospital food by using spices and salts of herbs, which enhance the flavor and improve the palatability of diets.